Analisis Kualitas Pelayanan dan Citra terhadap Minat dengan Kepuasan sebagai Variabel Intervening - Santosa, Teguh; Susbiyani, Arik; Cahyono, Dwi (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The purpose of this study was to determine directly or indirectly the effect of workload and WFC on employee performance through organizational commitment as an intervening variable at the village empowerment office of Bondowoso Regency. The number of samples in this study was 110 using the Nonprobability Sampling Technique. The analysis technique used is Structural Equation Model (SEM) using Pls 7.0 The main finding of this study is to examine the coefficients of direct and indirect paths to improve employee work through the WFC workload variables, organizational commitment and employee performance. Keywords: Service Quality, Image, Interest, Satisfaction